2018
DOI: 10.1002/adsc.201801185
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Iodine(III)‐Mediated Regioselective Cyanation of Quinoline N‐Oxides with Trimethylsilyl Cyanide

Abstract: A regioselective cyanation of quinoline N-oxides with trimethylsilyl cyanide was developed by using (Diacetoxyiodo) benzene (PIDA) as mediated hypervalent iodine(III) reagent under metal-free and base-free reaction conditions to obtain 2-cyanoquinolines. The efficient PIDA reagent could play the role of an activator of the substrates and an accelerator of NÀO bond cleavage. The reaction system featured a wide range of substrate suitability and high yields. The procedure was enlarged gram-scale to synthesize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…of trimethylsilyl cyanide in dichloroethane (DCE) at room temperature. We observed no conversion after refluxing overnight (Table , entries 1 and 2) which was consistent with the reported literature . However, when dimethylformamide (DMF) was employed as the solvent rather than DCE, the conversion was slightly improved and the desired product was obtained with a modest 12% yield (entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…of trimethylsilyl cyanide in dichloroethane (DCE) at room temperature. We observed no conversion after refluxing overnight (Table , entries 1 and 2) which was consistent with the reported literature . However, when dimethylformamide (DMF) was employed as the solvent rather than DCE, the conversion was slightly improved and the desired product was obtained with a modest 12% yield (entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…Various reagents like dimethyl sulphate, [17] N,N-dimethylcarbamoyl chloride, [18] ethyl chloroformate, [19] benzoyl halides, [20] acetic anhydrides, [21] and MsCl, [22] have been used as activators for this purpose [more recently, Sun and coworkers used hypervalent iodine (III) [23] as an activating agent]. Various reagents like dimethyl sulphate, [17] N,N-dimethylcarbamoyl chloride, [18] ethyl chloroformate, [19] benzoyl halides, [20] acetic anhydrides, [21] and MsCl, [22] have been used as activators for this purpose [more recently, Sun and coworkers used hypervalent iodine (III) [23] as an activating agent].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sun and coworkers found that the reaction with quinoline N ‐oxides can be activated by the eco‐friendly and inexpensive hypervalent reagent PhI(OAc) 2 (PIDA, Scheme 95). [127] The reaction proceeds quickly, but is not efficient enough for pyridine N ‐oxides. Das's group successfully prepared 2‐cyanated pyridines and quinolines 317 under neat conditions at high temperatures either by conventional heating or microwave treatment (Scheme 96).…”
Section: Simple C2‐h‐functionalizationmentioning
confidence: 99%